Financial constraints and firm investment in Malaysia: an investigation of investment-cash flow relationship - Ismail, Mohd Adib; Ibrahim, Mansor; Yusoff, Mohammed; Zainal, Mohd Pisal (Faculty of Economics and Management, Universiti Putra Malaysia, 2010)
This paper investigates the presence of financial constraints among firms in Malaysia using firm level panel data analysis. The empirical results based on panel GMM demonstrate that financial constraints are present in the market, which indicate that the firms are unable to access to external forms of financing. In addition, the presence also signifies the presence of asymmetric information problem between the firm and its financer. Thus, the neoclassical investment theory which based on assumption of complete information such that only factor prices and technology determine firm’s desired capital stock is simply rejected. Eventually, their investments are much affected by fluctuations in their cash flows or retained earnings.